Release behavior, mechanical properties, and antibacterial activity of ciprofloxacin-loaded acrylic bone cement: a mechanistic study. (2nd August 2020) - Gandomkarzadeh, Marzieh; Mahboubi, Arash; Moghimi, Hamid Reza
Abstract: Objective: To evaluate the effect of ciprofloxacin concentration and cement geometry on release, mechanical, and antibacterial properties of PMMA bone cement. Significance: Cements are used in different geometries and drug concentrations. These can affect cement strength, drug release behavior, and its antibacterial activity. Methods: Antibiotic-loaded bone cement (ALBC) containing 2.5, 5.0, and 10.0 wt% ciprofloxacin were prepared as slab, rectangular prism and short cylinder. Drug release and compression strength of the cements were investigated for 28 days at 37 °C. The ALBC efficacies against prevalent bone infection bacteria, S. aureus, E. coli, and P. aeruginosa, were investigated. Drug determination was by HPLC. Results: A two-stage behavior of fast release through dissolution/diffusion (stage A; <96 h) and 2–5 times slower Fickian diffusion (stage B; 96–672 h) was observed. Significant differences for release rate were observed among different geometries in the order of cylinder > prism > slab, in correlation with systems' thickness, indicating lower drug depletion in thicker systems. Release rates were proportional to concentration for 2.5 and 5% systems. At 10.0% loading, however, apparently interconnected channels and higher porosity reduced the diffusional resistance and provided higher release rates than what expected from concentration increment. Growth of Gram-negative bacteria and S. aureus was inhibited at the lowest dose of drug over 1 and 48 h, respectively. ALBCs with 5.0 and 10.0% ciprofloxacin showed decrease of compression strength to below ISO standard. Conclusions: Different properties of acrylic cements are affected by geometry and drug concentration and should be considered for optimized drug therapy.